miR-146a-5p Plays an Oncogenic Role in NSCLC via Suppression of TRAF6 - Liu, Xiangdong; Liu, Bo; Li, Ruihua; Wang, Fei; Wang, Ning; Zhang, Maihe; Bai, Yang; Wu, Jin; Liu, Liping; Han, Dongyu; Li, Zhiguang; Feng, Bin; et al. (Frontiers in Cell and Developmental Biology, 2020)
Non-small cell lung cancer (NSCLC) is the most deadly cancer all over the world11, 40 due to its usually delayed diagnosis. Identification of biomarkers with high sensitivity, specificity and accessibility for early detection23, such as circulating microRNAs, is therefore of utmost importance5. In the present study, we identified significantly higher expression of miR-146a-5p in the serum and tissue samples of NSCLC patients than that of the healthy controls. In parallel, miR-146a-5p was also highly expressed in three human NSCLC adenocarcinoma-cell lines (A549, H1299 and H1975) compared to the human lung fibroblast cell line MRC-5. By dual luciferase reporter assay and manipulation of the expressions of miR-146a-5p and its target gene, tumour necrosis factor receptor-associated factor 6 (TRAF6), we showed that the functional effects of miR-146a-5p on NSCLC cell survival and migration were mediated by direct binding to and suppression of TRAF6. Overexpression of TRAF6 sufficiently reversed miR-146a-5p overexpression-induced cancer cell proliferation, migration and apoptosis resistance. Our data implied that miR-146a-5p-TRAF6 axis could be a promising diagnostic marker and a therapeutic target for NSCLC.